2013
DOI: 10.1016/j.athoracsur.2013.04.053
|View full text |Cite
|
Sign up to set email alerts
|

Risks Associated With the Transfusion of Various Blood Products in Aortic Valve Replacement

Abstract: Background:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
12
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 26 publications
1
12
1
Order By: Relevance
“…For heart surgery, there was an important shift in the type of surgery: although the total number of patients in this group was lower in Period 2, the number of procedures with a greater risk of blood loss was markedly higher. Again, the mean number of units transfused (4.7 units) and the transfusion rate for this subgroup (59%) are in line with data from the literature and did not change between the two periods. Third, an additional consequence of the variation in the case mix of those who undergo cardiac surgery may be an increase in the number of heavily transfused patients because, in this subgroup, cardiac patients represent the vast majority (about 70%).…”
Section: Discussionsupporting
confidence: 88%
“…For heart surgery, there was an important shift in the type of surgery: although the total number of patients in this group was lower in Period 2, the number of procedures with a greater risk of blood loss was markedly higher. Again, the mean number of units transfused (4.7 units) and the transfusion rate for this subgroup (59%) are in line with data from the literature and did not change between the two periods. Third, an additional consequence of the variation in the case mix of those who undergo cardiac surgery may be an increase in the number of heavily transfused patients because, in this subgroup, cardiac patients represent the vast majority (about 70%).…”
Section: Discussionsupporting
confidence: 88%
“…So, it seems that bronchopulmonary immaturity, hypoproteinemia, additional fluid retention worsens its inability to adapt the environment of systemic inflammatory response provoked by CPB, which might consequently aggravate the increase of permeability, pulmonary vascular resistant and the changes of lung surfactant, and exacerbate lung disturbances early after surgery [2,3,21]. Though transfusion of blood products during or after surgery had been proved to be a strong risk factor of acute lung injury and might associated with increased mortality in long-term follow-up [22-24], there were no significant differences of nadir HCT during CPB and incidence of transfusion early after surgery between two groups in our study. We proposed that the possible reasons might be the restrictive transfusion policy both in CPB circuit priming (only in patients with an estimated nadir HCT ≤25% during CPB) and after surgery (only in patients with Hb ≤ 7 g/dL or coagulation dysfuction), and routine use of ultrafiltration and CPB circuit residual blood salvage re-infusion in all the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Because the studies showing an association between transfusion and late mortality have not shown a cause-and-effect relationship, investigators have inferred a number of mechanisms to explain the apparent association between RBC transfusions and mortality; these include immunomodulation or microcirculatory injury from transfused RBCs [2][3][4]. However, the lack of a similar mortality association in patients not undergoing CABG suggests that the mechanism of RBC transfusion causing death is not generalizable to all types of surgical procedures but instead may be specific to CABG [1][2][3][4][5].…”
mentioning
confidence: 94%
“…Interestingly, this effect is most pronounced among patients undergoing isolated coronary artery bypass grafting (CABG). Previous reports have found limited risk associated with transfusions among patients undergoing isolated valve operations, suggesting that intrinsic factors unique to CABG (relative to valve operations) may in part explain the role of transfusion in this setting [1][2][3][4][5]. Because the studies showing an association between transfusion and late mortality have not shown a cause-and-effect relationship, investigators have inferred a number of mechanisms to explain the apparent association between RBC transfusions and mortality; these include immunomodulation or microcirculatory injury from transfused RBCs [2][3][4].…”
mentioning
confidence: 98%